EXPERIÊNCIAS TURÍSTICAS EM CONTEXTOS RELIGIOSOS E DE PEREGRINAÇÃO. UMA ABORDAGEM NA ÓTICA DO CONSUMIDOR DOS CAMINHOS DE SANTIAGO - Machado, Tânia Gomes (2018)
Pilgrimage tourism, of which the Camino de Santiago is also an example, has shown a growing interest in a tourism segmentation perspective, and is therefore included in tourism planning activities. Considering the economic effects of the existence of these pilgrimage routes, as well as the way in which these same routes are positioned next to the market, there is a growing importance and orientation for different experiential searches. However, the existing literature seems to reveal a gap in planning and management of tourism destinations in specific tourism contexts (eg religious tourism and pilgrimage). This study aims to understand the behavior of the consumer in the context of pilgrimage tourism, in the particular case of the Santiago Way. As such, the main objective of this master's thesis was to understand the profile of the consumers of the Santiago de Compostela roads, as well as to understand the behavior of this type of tourist. A conceptual model was developed to study a set of previously presented hypotheses that were tested based on the data collected through the questionnaires collected from the pilgrims from Santiago de Compostela. The purpose of this dissertation is to understand the role of certain affective bonds in the behavioral intentions of tourist consumers, in particular as regards the motivations that lead tourists to carry out the various routes of the Santiago Way. The understanding and analysis of the dimensions of the present study may be, in parallel with the conclusions obtained, a tool to support the management of pilgrimage routes.